Work Hazards and Social Class among ‘successful’ ALMP-Participants in Norway (Journal of Comparative Social Work, 2025)
Background and research question. Studies of the outcomes of participation in Active Labour Market Programmes (ALMP) focus primarily on employment status or earnings. Few studies address the social class and work environment that “successful” ALMP-participants transit to. Little is also known about whether participation in different types of ALMPs leads to different social classes and work environments. This is unfortunate since many ALMP participants have health challenges and reduced work ability and thus are particularly susceptible to poor working conditions. Data and methods: Using Norwegian register data, we examined social class and exposure to hazardous working conditions, measured by a Mechanical Job Exposure Matrix and a Psychosocial Job Exposure Matrix, that characterised the jobs of “successful” ALMP participants, compared with the general work force. Results: We found that both mechanical and psychosocial job exposures in male ALMP-participants were higher than those of the general work force. For female participants, mechanical exposures were higher than the average level in the general work force, while psychosocial exposures were lower. Further, job exposures differed by ALMP type, but after adjustment for age, education and social class, only negligible differences in job exposures between ALMP types remained. Social class contributed to variation in both mechanical and psychosocial job exposures, most for mechanical exposures among male participants, and least for psychosocial exposures among female participants. Conclusion: Compared with the general working population, former ALMP participants, regardless of what type of programmes they participated in, entered lower social classes and tended to face more hazardous work environment.